(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The essence, nature, interrelationships, and mechanisms of interaction of units at the syntactic level are studied as central issues in the science of language, in particular syntax. Although most of the units in the syntactic structure and their interrelationships have been agreed upon in linguistics, the issue of parentheses, which occupies a special place at this level, has not yet been resolved in Uzbek linguistics, as in other linguistics. However, it is impossible to bypass the phenomenon of parentheses in order to perfectly describe and describe the communicative-syntactic structure of language, and more precisely, the syntax of text.